Implementation Of Dot Matrix Max7219 For Product Price Display - saputro, galib asbie; anshory, izza; Syahrorini, Syamsudduha; Sulistiyowati, Indah (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2024)
The advancement of technology has strengthened the role of retail businesses as providers of products and services that are not only efficient but also responsive to market changes. In this context, the implementation of technological solutions such as the Dot Matrix MAX7219 for product price display has become increasingly important in improving operational efficiency and customer experience. This research investigates the development and implementation of such a system using the Wemos D1 Mini microcontroller as the central control unit. Experimental methods were used to design, test, and update the system, focusing on the system's response to changes in product prices and WiFi connection stability. The test results show that the system is able to display prices quickly, accurately, and responsively, while also having an adequate WiFi connection range. The practical implications of this research include the potential adoption of this solution by retail businesses to enhance operational efficiency and customer experience. However, continuity in system development and maintenance remains necessary to ensure the sustainability and success of the implementation in the long term.